TECTONOSTRATIGRAPHY AND POST-MORTEM ANALYSIS OF HYDROCARBON EXPLORATION WELLS BLOCK X, SPERMONDE BASIN, SOUTH SULAWESI - Wargaliyasa, Gatra
Spermonde basin is potential sedimentary basin that has not proven yet to be commercial hydrocarbon accumulation. Hydrocarbon exploration activity has been beginning since 1970’s marked by seismic acquisition and exploration wells drilling, nevertheless all of the wells status are plug and abandoned now due to lack of hydrocarbon accumulation, however there are hydrocarbon shows from certain depth in wells. Based on that condition, it is interesting to determine the post-mortem analysis of hydrocarbon exploration wells. Methodology that has been using in this research are tectonostratigraphy succession analysis and petroleum system evaluation. Based on tectonostratigraphy and petroleum system evaluation, lack of hydrocarbon accumulation causes could be identified. Basin evolution of Spermonde basin started with rifting from Paleocene that forming NW-SE half graben, same orientation rifting occured again during Late Eocene-Oligocene, NE-SW compression regime tectonic was generating inversion geometry in Miocene. Tectonostratigraphy packages consist of Pre-Rift, Early Syn-Rift 1, Maximum Syn-Rift 1, Post-Rift 1, Syn-Rift 2, Post-Rift 2, Syn-Inversion and Post-Inversion. Based on petroleum system evaluation, Maximum Syn-Rift 1 and Post-Rift 1 have defined as a good potential source rock (TOC > 1), it is a type III kerogene oil and gas prone with a hydrocarbon window of maturity at 6600 feet and have 2000 Tcf and 320.000 MMbbl for hydrocarbon generated estimation of source rock. Primary migration (expulsion) efficiencies are 1900 Tcf for gas dan 160.000 – 224.000 MMbbl for oil. Potential reservoir rock interval is Maximum Syn-Rift 1. Potential seal rock is Post-Rift 1 and shale of intraformation within maximum syn-rift 1. Structural traps that could be determined was anticline. Lacks of hydrocarbon accumulation in general were caused due to migration pathway was not moved toward to closure, poor seal capacity and inappropriate wells position.